HIV-1 suppression and rare dolutegravir resistance in antiretroviral-experienced people with HIV in Liberia - James Soka Moses; Alice K. Pau; Safia Kuriakose; Greg Grandits; Cavan Reilly; Brad T. Sherman; Weizhong Chang; Lisheng Dai; Muhammad A. Khan; Helene Highbarger; Moses Mannah; Johnathan McCullough; et al. (Communications Medicine)
Abstract Background Increasingly, persons with HIV in Liberia are receiving antiretroviral therapy containing the integrase strand-transfer inhibitor (InSTI) dolutegravir (DTG), but the prevalence of and factors associated with virologic failure and HIV drug resistance (HIVDR) remain unknown. Methods Cross-sectional analysis of 2019–2022 enrolment data from 1276 persons with HIV in the HONOR cohort included sociodemographic information, plasma viral loads (pVL), CD4 counts, and HIVDR testing by next generation sequencing in participants with virologic failure (pVL≥1000 copies/mL). Results Of the 1201 participants with pVL results, 72% are female and median age is 42 (interquartile range [IQR] 35–50) years. All are on ART (median 6.1 [2.1–11] years): 74% on DTG-based and 23% on non-nucleoside reverse transcriptase inhibitor (NNRTI)-based regimens. Ninety (7.5%) had virologic failure; 970 (81%) are suppressed (<40 copies/mL). Virologic failure is less prevalent with DTG- versus NNRTI-based regimens (5.3% vs. 14%, adjusted prevalence ratio [aPR]=0.3, 95% confidence interval [CI] 0.2–0.5) and is associated with age <50 years, CD4 count <200 cells/µL, and hemoglobin <11 g/dL. In 70 participants with virologic failure and successful sequencing, HIVDR prevalence is 81% for any ARV, 5.7% for InSTIs, 79% for NNRTIs, and 61% for nucleos(t)ide reverse transcriptase inhibitors (NRTIs). Intermediate-to-high resistance to ≥1 NRTI in current ART is less prevalent with DTG+2NRTIs than NNRTI+2NRTIs regimens (aPR = 0.5, 95%CI 0.3–0.8). Conclusions Most participants in the cohort are virologically-suppressed. Among those with virologic failure, HIVDR prevalence is high to NRTIs and NNRTIs, but low to InSTIs. Ongoing evaluation is necessary to determine the durability of DTG-based ART.